Keberhasilan Pelaku Wirausaha dalam Mengembangkan Usahanya di Destinasi Wisata Danau Cipondoh Kota Tangerang, Provinsi Banten - Devita Gantina; Anita Swantari; Andhalia Liza Marie; Mohammad Syaltut Abduh; Heny Ratnaningtyas Ratnaningtyas (Tourism Scientific Journal, 2022)
This study aims to determine the effect of entrepreneurship education, family environment and personality on business success. This type of research is descriptive research with a quantitative approach with multiple regression analysis using Smart PLS. The location of this research was conducted at the tourist destination of Lake Cipondoh. The sampling technique uses saturated sampling because the total population is the same as the number of samples, namely 63 entrepreneurs in the Lake Cipondoh tourist destination. The results of the study partially show that entrepreneurship education, family environment and personality have a significant effect on business success. Entrepreneurship education has a significant effect on business success, because in entrepreneurship education there is provision of skills in the form of self-development which can be understood as an effort to apply an entrepreneurial spirit and mentality. The family environment has a significant effect on business success, because from the family environment, entrepreneurs are inspired and receive support for entrepreneurship. namely high fighting power, courage and self-confidence, overcoming fear and anxiety, controlling every decision yourself, having an independent nature not depending on others. The value of the coefficient of determination of business success is 69.8%, the variable of business success is influenced by the variables of entrepreneurial education, family environment and personality.